Characterization of 12-bit SAR ADC for wireless applications - Bhagyalakshmi Manjunatha (2018)
Analog to Digital converters at Intel are used for different applications namely, calibration of internal components of a firmware, accurate voltage/current measurements etc. Meeting the simulation results with the practically obtained results for an ADC gets difficult when the resolution of ADC is high (12 bits and above). High resolution ADCs require higher resolution (resolution higher than the ADC to be tested) equipment for characterization. The behavior of ADC is limited by various factors among which, the supply voltages to the system and temperature of the system are critical. The dissertation aims to meet the specification values for a 12 bit SAR ADC in all specified supply voltages and temperatures. The ADC is characterized for its offset error, gain error, Integral Non Linearity, Differential Non Linearity, Signal to Noise Ratio, Spurious Free Dynamic Range and Effective Number of Bits. To ensure optimum behavior under worst-case scenarios, the characterization is performed for multiple corners (Fast, Typical and Slow). The ADC used for characterization is equipped with multiple modes of operation, namely periodic, manual and automatic. Since the application demands the SAR ADC to be configured in the automatic mode of operation, the characterization is done exclusively for this mode. The ADC employs an internal averaging method to generate the binary codes. Using a source meter, the ADC data is collected across three distinct temperatures and post-processed using MATLAB.